O054 Genioglossus neural drive and upper airway dilation in people with obstructive sleep apnoea during wakefulness. (9th November 2022) - Jugé, L; Liao, A; Yeung, J; Knapman, F; Burke, P; Brown, E; Gandevia, S; Eckert, D; Butler, J; Bilston, L
Abstract: Introduction: Genioglossus neural drive and the ensuing tongue dilatory movement may be dissociated in obstructive sleep apnoea (OSA), but this has not been studied. This study aimed to investigate this relationship and its potential role in OSA pathophysiology. Methods: During awake nasal breathing in the supine position, inspiratory tongue dilatory movement, quantified with tagged magnetic resonance imaging, and inspiratory peak genioglossus electromyography (EMG) normalised to the maximum voluntary contraction (tongue protrusion), were measured in 4 tongue neuromuscular compartments from 8 controls [apnea-hypopnea index (AHI)<5 events/h] and 34 patients with untreated OSA [AHI>10 events/h]. Results: Although larger inspiratory dilatory movement was associated with increased drive to genioglossus (partial Spearman, r=0.23, p=0.016, n=115/68% of compartments), in 14% of the compartments (n=16), there was a large dilatory (>1mm) movement but minimal EMG (<4th percentile). This occurred only in the horizontal compartment. In another group of 18 compartments (16%), there was a large peak EMG (>4th percentile) but minimal dilatory movement (<1mm). This occurred more commonly in the oblique compartments. Dissociation between the amplitude of the peak EMG and inspiratory tongue dilatory movement was most commonly seen in severe OSA patients (AHI>30 events/h, Fisher's exact test, p=0.047). Conclusions: Inspiratory tongue dilatory function generally remains closely linked to muscle drive during wakefulness, with larger movement associated with higher peak EMG. However, for approximately one-third of the neuromuscular tongue compartments, neural drive was dissociated from the dilatory motion in severe OSA patients. This may contribute to OSA pathogenesis and have implications for neural stimulation therapy targets.